A New Definition Method of Wind Power Ramp Sections - Honghai Kuang; Wang Jianhui; Hanchao Zhang; Hao Zhong; Guoping Zhu (IEEE Access, 2020)
A new definition method of ramp sections is proposed. Firstly, the extreme point extraction algorithm is designed. The results show that the extreme value sequence can not only achieve data compression, but also provide data for the definition of the ramp section. Secondly, several typical recognition methods of wind power ramp are compared. The results show that the ”event” as the unit of analysis is not possible to effectively distinguish between the ramp process and the transient process in the ramp event, which causes the prediction error of the ramp duration. Also, the non-representation of the threshold setting will also cause errors in the prediction and recognition of complex ramp events. In this article, the concepts of ramp section, slope point(SP) and stagnation point(STP) are introduced to realize the segmentation processing and analysis of ramp events, which can effectively distinguish the ramp process and transient process in ramp events and provide a strong guarantee for the accurate prediction of the ramp duration. In addition, the mathematical statistics method of cumulative probability is utilized to discuss the threshold setting. The ramp situation of a wind farm in Yunnan in 2014 is further identified and analyzed, and on this basis, the characteristics of the ramp sections are investigated, whose results show the applicability of this new definition.